THE RELATION BETWEEN KNOWLEDGE OF OLD AGE WOMAN WITH LEVEL OF ANXIETY PERIODE OF MENOPAUSE IN PANTI JOMPO YAYASAN NURUL JANNAH WERDHA - Yenni Merdeka Sakti; Miskah Afriani; Asrul Asrul (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
The Period of menopause represent one of the period to feeling concerned about woman in her life cycle, this matter is caused by dread of change will that happened when entering a period of menopause. In this period will happened change of physical and psychological. That is needed a knowledge which enough to be more recognizing and can handle changes that happened. Target of this research is to know relation between knowledge of old age woman with level of anxiety period of monepause in Panti Jompo Yayasan Nurul Jannah Werdha. This research use analytic survey with transversal surgical operation (sectional cross). Research sampel amount to 37 responder people representing old age woman. Measuring instrument that used is kuesioner that is kuesioner mount anxiety a period of menopause and kuesioner knowledge of old age woman about menopause. Data analysis use Test of Chi-Square with meaning level of a = 0,05. Result of research is descipted that knowledgeable responder less is owning of heavy anxiety counted 47,1% (8 responder people), knowledgeable responder enough have heavy anxiety counted 83,3% (5 responder people), and knowledgeable responder of goodness have heavy anxiety counted 50,0% (7 responder people). While statistical test by using test of Chi-Square obtained by value of p value 0,614 meaning bigger than a = 0,05. This matter show there is no relation having a meaning between knowledge of old age woman with anxiety at a period of menopause in Panti Jompo Yayasan Nurul Jannah Werdha.